2020
DOI: 10.1177/1708538120936421
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of next generation sequencing–liquid biopsy on cell-free DNA as a novel non-invasive diagnostic tool for Klippel–Trenaunay syndrome

Abstract: Objectives Somatic mosaicism of PIK3CA gene is currently recognized as the molecular driver of Klippel–Trenaunay syndrome. However, given the limitation of the current technologies, PIK3CA somatic mutations are detected only in a limited proportion of Klippel–Trenaunay syndrome cases and tissue biopsy remains an invasive high risky, sometimes life-threatening, diagnostic procedure. Next generation sequencing liquid biopsy using cell-free DNA has emerged as an innovative non-invasive approach for early detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…K Zenner extracted cfDNA from the plasma and cystic fluid of patients with venous, lymphatic, and arteriovenous malformations, and variants were detected for the first time [ 13 ]. Subsequent studies of the application of cfDNA in arteriovenous malformations and Klippel–Trenaunay syndrome further validated the investigation of cfDNA-based molecular diagnostics and provided a noninvasive method to initiate targeted therapy for patients with vascular malformations [ 14 , 15 ]. However, there is currently no report of cfDNA genetic analysis on MS associated with SCH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…K Zenner extracted cfDNA from the plasma and cystic fluid of patients with venous, lymphatic, and arteriovenous malformations, and variants were detected for the first time [ 13 ]. Subsequent studies of the application of cfDNA in arteriovenous malformations and Klippel–Trenaunay syndrome further validated the investigation of cfDNA-based molecular diagnostics and provided a noninvasive method to initiate targeted therapy for patients with vascular malformations [ 14 , 15 ]. However, there is currently no report of cfDNA genetic analysis on MS associated with SCH.…”
Section: Discussionmentioning
confidence: 99%
“…More sensitive and noninvasive diagnostic methods may provide adequate information for molecular characterization. In recent years, the clinical utility of cell-free DNA (cfDNA) has been explored in many kinds of vascular malformations [13][14][15][16]. However, there is currently no report of cfDNA genetic analysis on MS associated with SCH.…”
Section: Introductionmentioning
confidence: 99%
“…A PIK3CA single gene test was reported for KTS [4,6] for determining a targeted molecular diagnosis through a biopsy of affected tissues [3,7]. Luks et al found that PIK3CA mutations were present at low frequencies (<10%) in many affected tissue samples [6].…”
Section: Discussionmentioning
confidence: 99%
“…Luks et al found that PIK3CA mutations were present at low frequencies (<10%) in many affected tissue samples [6]. Due to the inaccessibility or invasiveness of a solid biopsy, next-generation sequencing of cell-free DNA has recently been used as a non-invasive diagnostic tool for KTS [3]. In this study, we performed WGS to explain the difficulty in enriching only PIK3CA mutations and affected tissue from biopsies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation